Maternal health care services utilization and associated factors among women in Zoba Maekel, Eritrea 2022: a community based study (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2024)
Introduction: Studies reveal that regular utilization of maternal health care services reduces maternal morbidity and mortality in which these services are affected by complex factors which may be similar across populations.Methods: A community based cross sectional study was conducted from February to May of 2022. A total of 607 women who gave birth in the last 2 years and residing in the area for at least 6 months were selected by two stage cluster sampling technique. A predesigned and pretested questionnaire was used to collect data via face to face interview technique. Chi-square test and multivariable logistic regression were used for data analysis using SPSS (Version 26).Results: Magnitude of maternal health care services utilization was found as; attending antenatal care 99.9%, institutional delivery 99.3% and postnatal care 91.4%. The majority (91.4%) were aware of postnatal care. The proportion (91.5%) of women who utilized postnatal care among those with awareness about it was significantly greater (p